The Ilio-Pelvic colon Peruvians. Introduction - Escudero Franco, Francisco (1965)
The Sigmoid volvulus Asa is one of the common causes of Intestinal Occlusion in our environment, as evidenced by publications surgeons acting ' in various regions of the country. The casuistic can appreciate that in the provinces of the Sierra , where there is the highest percentages . This feature contrasts with the fact observed on the coast, where Asa Sigmoid volvulus , is not reported as a cause of acute abdomen , but in low proportion . The papers presented at the V Inter-American Congress of Surgery in La Paz, Bolivia , in 1948 , and the Medical-Surgical II Peruvian-Bolivian Day in Lima, Peru , in 1962 , are a real Symposium incidence of sigmoid volvulus handle Undine in the settler , also observed in Bolivia , Chile and Argentina NO. Our surgeons agree in principle , as an etiologic factor , the greater length of the sigmoid loop concomitantly with the approach of the two pillars of mesosigma , considered by most writers as a fundamental anatomical element in the production of sigmoid volvulus . However, the frequency of this morphological feature in indomestizo group height , puts the problem in terms of the etiology of Dolicosigma , subsisting discussion in our surgical environment , on its interpretation : either as racial factor or as a dietary factor occasionally food , adding the reduced air pressure.